The importance of the interpretation of the norms governing public administration for the proper identification of discretion - Blanchet, Luiz Alberto (Universidad Nacional del Litoral, 2019)
Unprepared, the majority of Brazilian public agents usually are unaware to distinguish law and juridical norm, they ignore the interpretation techniques. As a result, those public officials are unable to identify the existence and limits of discretion in a specific norm. They despise the peculiarities of each individual case (concrete reason of de administrative procedures) and they extend the limits of a discretion that often doesn’t exist. However, inaptitude is not the only obstruction of the public interest due satisfaction, there are other impediments: imprudence or rashness, hurry, indolence, personal vanity, adherence to individual power, carelessness, avidity, covetousness and corruption. The bad public administrators that damage advisedly the society dispute with those who damage inadvertently the collectivity. Public agents must know how to interpret the norms, but they must interpret also the concrete cases (concrete reasons of de administrative fulfilments),  because both interpretations are important to identify the true limits of administrative discretion. In each individual concrete case, the discretion is lesser than it were in the norm in thesis, furthermore the administrative discretion manifests itself in a different way as the legally relevant peculiarities of each situation to be met.